Innovation, intelligence and tourism, keys to destination management - Mata, Austin (2013)
Technological innovation in the service of more complex and diversified tourism is a challenging macro for a consolidated destination such as it is Margarita island because it involves the study of social indicators, economic, environmental, cultural, and technological requirements attached to operational networks that make efficient and competitive every tourist cluster in the current environment of the information society. That is why it was proposed as a general objective to propose an indexing system for the intelligent management of tourist destinations. The research design was field, transactional, with the exploratory level, for this we characterized the technological key axes of the municipalities on Margarita Island, building on the methodology of "Smart Cities". The main results of this investigation it was observed that there is on Margarita Island enough information to build a virtually executable database, this enables intelligent planning a destination unlike other large countries like China must adapt rapidly to new technological demands on the target under study the possibility of rethinking the intelligent model to follow. In this same vein, it was able to achieve in this first study, an indexing system that involves tourism with government services, intelligent infrastructure and economy, and it is concluded that it is essential to prompt management reduced use of natural resources, integration of communities to tourism, reduced pollution levels, insecurity, proper use of water resources, capacities, expansion of leisure, recreation, transports, health care and the need to incorporate global wireless networks